Linguistic Analysis of Trademarks of Selected Buffet Restaurants in SM Mall of Asia, Manila - Ubaldus Djonda; Angelita R. Mendoza (SOSHUM : Jurnal Sosial dan Humaniora, 2022)
Trademarks are important for business establishments because they express the origin and quality of the companies, but it is not always easy to know and employ linguistic elements to craft good trademarks. Thus, to see the linguistic characteristics and strength of trademarks, the study has an objective to examine the trademarks of selected buffet restaurants at SM Mall of Asia, in Pasay, Metro Manila, Philippines. The data were taken from nine buffet restaurants. The analysis was done by referring to Shuy’s (2002) linguistic tools and Butters’ (2010) framework. The findings reveal that the linguistic characteristics mainly used by the buffet restaurants were lexicography, phonetics, morphology, and semantics. In terms of lexicography, most trademarks have their etymological meaning and historical development in the dictionaries, except Charaptor and Yakimix, which are coined words. In phonetics, the trademarks have phonetic characteristics of 1-3 syllables. Then the morphological analysis shows that the trademarks consist of noun phrases, affixation, and word formation (clipping). In semantics, five trademarks do not have synonyms and polysemy; three have synonyms, and two have polysemy. In terms of strength, the trademarks were classified from the weak to the strongest as follows: Buffet 101 (descriptive); Cabalen, La Fiesta, Oceana (suggestive); Four Seasons, Vikings (arbitrary); and Charaptor, GEN, Yakimix (fanciful). The findings imply that business owners need to create their companies’ trademarks in arbitrary or fanciful categories.